2012
DOI: 10.1124/dmd.111.042465
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Systems Involved in the Metabolism and the Disposition of Xenobiotics: Comparison between Human Intestinal Biopsy Samples and Colon Cell Lines

Abstract: ABSTRACT:Intestinal cell lines are used as in vitro models for pharmacological and toxicological studies. However, a general report of the gene expression spectrum of proteins that are involved in the metabolism and the disposition of xenobiotics in these in vitro systems is not currently available. To fill this information gap, we systematically characterized the expression profile of 377 genes encoding xenobiotic-metabolizing enzymes, transporters, and nuclear receptors and transcription factors in intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 38 publications
4
55
0
Order By: Relevance
“…Nucleosides and their analog drugs generally have hydrophilic properties and diffuse slowly across the cell membrane; therefore, nucleoside transporters expressed in the small intestine largely contribute to their oral absorption (Endres et al, 2009;Okayama et al, 2012;Ishida et al, 2013). Previous studies reported that Caco-2 cells did not express CNT1, CNT2, or CNT3 (Ward and Tse, 1999;Bourgine et al, 2012), which was consistent with the very low expression of CNTs observed in our study (Fig. 3B).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nucleosides and their analog drugs generally have hydrophilic properties and diffuse slowly across the cell membrane; therefore, nucleoside transporters expressed in the small intestine largely contribute to their oral absorption (Endres et al, 2009;Okayama et al, 2012;Ishida et al, 2013). Previous studies reported that Caco-2 cells did not express CNT1, CNT2, or CNT3 (Ward and Tse, 1999;Bourgine et al, 2012), which was consistent with the very low expression of CNTs observed in our study (Fig. 3B).…”
Section: Discussionsupporting
confidence: 92%
“…3) have been well documented in previous studies (Schmiedlin-Ren et al, 1997;Sun et al, 2002;Bourgine et al, 2012). In this study, the expression profile of mRNA for the P450/UGT isoforms in HIECs was similar to that in Caco-2 cells, except for CYP2C9, CYP2C19, UGT1A6, and UGT2B7.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, several proteins, including transporters, were over-or underexpressed. Bourgine et al ( 2012 ) compared the expression of 377 genes in HT29 and other intestinal cell lines that are used as in vitro models of the epithelium with the corresponding tissue biopsy. The results showed that differentiated HT29 cells and human colonic tissues do not appear to be signifi cantly different.…”
Section: Relevance To Human In Vivo Situationmentioning
confidence: 99%
“…Although LS180 cells exhibit basal and inducible CYP3A4 activity (Zheng et al, 2012), they are thought not to form tight junctions in culture. In contrast, T84 cells are known to form tight junctions (Dharmsathaphorn et al, 1984); however, expression of CYP3A4 by T84 cells is controversial (Juuti-Uusitalo et al, 2006;Bourgine et al, 2012), and its inducibility has not been reported. It is worth noting that this cell line expresses pregnane X receptor (PXR), which is one of the important nuclear transcription factors mediating CYP3A4 induction.…”
Section: Introductionmentioning
confidence: 99%